#### Answer

$y = \dfrac{x}{4} - 3$

#### Work Step by Step

$(y-(-3))=\dfrac{1}{4}(x-0) $
$y+3 = \dfrac{1}{4}x$
$y = \dfrac{x}{4} - 3$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$y = \dfrac{x}{4} - 3$

$(y-(-3))=\dfrac{1}{4}(x-0) $
$y+3 = \dfrac{1}{4}x$
$y = \dfrac{x}{4} - 3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.